Kant's thinker - Kitcher, Patricia (New York ; Oxford : Oxford University Press, 2011)
'Kant's Thinker' examines the 'Critique of Pure Reason' and gives an account of the relation between cognition and self-consciousness.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Kant, Immanuel, -- 1724-1804.; Self-knowledge, Theory of